(untitled) (Research, Society and Development, 2022)
Environmental Health Surveillance (VAS) has an institutional competence of management of the national environmental surveillance system and with the purpose of exercising surveillance of environmental risk factors that affect the population’s health. Objective this study is to analyze the dissemination of health prevention and health promotion actions carried out by VAS, from 2008 to 2017, in the municipality of Chapecó, SC. The documents analyzed were those produced and disseminated by the Press Office of the municipality, made available on Digital Versatile Disc (DVD) with clips of the actions published by the press. The study analyzed 681 media articles, most of which were journalistic articles (40.6%), followed by photos of stock records (16.7%) and radio articles (13.8%). It presents the sectors involved and the thematic axes of the actions and media campaigns represented, especially by epidemiological information, health education, community awareness and home visits. The highest intensity of publications was between December and April, due to the infestation by the Aedes aegypti mosquito and the risk for dengue transmission. Journalistic media are strong allies as a communicative strategy for health actions to be successful. In the same way, intersectorality is shown to be indispensable for the effectiveness of health promotion actions and disease prevention. They bring health services closer to the population, provide social participation in actions and contribute to transparency in service provision.